Organizational Citizenship Behavior and Job Satisfaction from The Nurses' Perspective - Ashwaq T. Al-Ahmadi; Sabah M. Mahran (Evidence-Based Nursing Research)
research in Saudi Arabia has been published investigating organizational citizenship behavior among nurses. In addition, job satisfaction has been identified as the main solution to the high turnover rate among nurses in Saudi Arabia and one of the factors that could affect organizational citizenship behavior.